Women Empowerment in Veterinary Field: A Review (International Journal of Scientific Research and Management (IJSRM), 2017)
Women Empowerment itself elaborates that Social Rights, Political Rights, Economic stability, judicial strength and all other rights should be also equal to women. There should be no discrimination between men and woman. In fact animal Husbandry is becoming feminized. About 70% of the agricultural workers, 69% of workforce engaged in livestock sector and 80% of the food a strong desire to do something positive is an inbuilt quality of entrepreneurial women, who is capable of contributing values in both family and social life. Women should now there fundamental and social rights which they get once they born. Empowering women to participate fully in economic life across all sectors is essential to build stronger economies, achieve internationally agreed goals for development and sustainability, and improve the quality of life for women, men, families and communities.